2019
DOI: 10.3389/fphys.2018.01865
|View full text |Cite
|
Sign up to set email alerts
|

The Promise of Stochastic Resonance in Falls Prevention

Abstract: Multisensory integration is essential for maintenance of motor and cognitive abilities, thereby ensuring normal function and personal autonomy. Balance control is challenged during senescence or in motor disorders, leading to potential falls. Increased uncertainty in sensory signals is caused by a number of factors including noise, defined as a random and persistent disturbance that reduces the clarity of information. Counter-intuitively, noise can be beneficial in some conditions. Stochastic resonance is a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 121 publications
0
14
0
Order By: Relevance
“…It has been shown that the presence of perturbations and surface irregularities leads to increased muscle activation, which may effectively stimulate strength gains over time (Munoz-Martel et al, 2019 ). Furthermore, there is evidence that the presence of fluctuations and disturbances in the neural processing of sensory inputs to motor outputs can improve motor behavior (Faisal et al, 2008 ; Sejdić and Lipsitz, 2013 ) and balance performance (Priplata et al, 2003 ; Aboutorabi et al, 2018 ; White et al, 2019 ), and may facilitate motor learning and adaptation (Faisal et al, 2008 ; Van Hooren et al, 2019 ). The results of this intervention showed that after 14 weeks of dynamic stability training in the presence of perturbations by unstable surfaces, both strength and balance recovery performance were significantly improved.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the presence of perturbations and surface irregularities leads to increased muscle activation, which may effectively stimulate strength gains over time (Munoz-Martel et al, 2019 ). Furthermore, there is evidence that the presence of fluctuations and disturbances in the neural processing of sensory inputs to motor outputs can improve motor behavior (Faisal et al, 2008 ; Sejdić and Lipsitz, 2013 ) and balance performance (Priplata et al, 2003 ; Aboutorabi et al, 2018 ; White et al, 2019 ), and may facilitate motor learning and adaptation (Faisal et al, 2008 ; Van Hooren et al, 2019 ). The results of this intervention showed that after 14 weeks of dynamic stability training in the presence of perturbations by unstable surfaces, both strength and balance recovery performance were significantly improved.…”
Section: Introductionmentioning
confidence: 99%
“…These approximate PDFsf o η implies a bona fide random noise, rather than a constant bias. Moreover, substituting the obtained approximate optimal noise PDFsf o η into (17), the corresponding MSE values of R NE (x) are reduced to 0.0448, 0.0267 and 0.0536, as listed in Table 1, which are almost equal to the corresponding MSEs achieved by the MMSE estimatorθ ms (x).…”
Section: Noise Benefits In Identical Sensorsmentioning
confidence: 88%
“…From (34), we deduce that R NE in (17) is a monotonically decreasing function of the sensor number M , when the observation data x and the added noise are given. Furthermore, for a sufficiently large number M → ∞, the MSE R NE in (17) can be simplified as…”
Section: Appendix C Proof Of Theoremmentioning
confidence: 99%
See 1 more Smart Citation
“…Stochastic resonance is one such phenomenon in which white noise is introduced to boost a subthreshold signal to cross a receptor's sensory threshold; therefore, improving the system's sensitivity to detect the subthreshold proprioceptive information (Nobusako et al, 2018). Stochastic resonance can be defined as adding a weak input signal of noise to an already weak signal resulting in a stronger resultant signal that can surpass the sensory threshold of a neuron's receptor (White, Babič, Trenado, Johannsen, & Goswami, 2019). This can allow useful information to pass to the central nervous system and allow for an appropriate response and balance restoration.…”
Section: Introductionmentioning
confidence: 99%